Population Dynamic And Effects Of The Invasive Species Ctenophore Mnemiopsis Leidyi In The Southern Caspian Sea - Roohi, Aboulghasem (2009)
In this study, M. leidyi population, plankton abundance, biomass and species composition and interaction between environmental and biological characteristics were evaluated in the Iranian coasts of the Caspian Sea from 2001 until 2006. Dalam kajian ini, populasi M. leidyi, kelimpahan plankton, biojisim dan komposisi spesies serta interaksi antara persekitaran dan aspek biologi telah dikaji di persisiran pantai Laut Caspian, Iran pada tahun 2001 hingga 2006